Effect of Sowing Dates on the Germination and Seedling Growth of Cedrus deodara and Pinus halepensis - Khan, M. A.; Mughal, A. H.; Mughloo, Javeed (Indian Forester, 2007)
A nursery trial of Cedrus deodara and Pinus halepensis with nine different sowing dates spread over autumn, winter and spring was conducted during 2002-2003. Germination in case of Cedrus deodara was better where seeds were sown in the month of February, but in Pinus halepensis sowing dates did not affect the germination up to 1st February. Survival percentage of seedlings was more in seeds sown in the first fortnight of February. Time taken for completion of germination decreased as sowing proceeded from autumn to spring. Except for diameter in Pinus halepensis seedling development in terms of height and diameter was also better in seeds sown in the first fortnight of February. Thus in order to get good germination, better survival and reduce nursery expenditure seeds should be sown in the nursery in the first fortnight of February (winter) instead of sowing seeds in the autumn season. Development of seedlings is also better in case seeds are sown in February (winter).